Genomic and secretomic analyses of Blastobotrys yeasts reveal key xylanases for biomass decomposition - Jonas Ravn; Amanda S. Ristinmaa; Scott Mazurkewich; Guilherme B. Dias; Johan Larsbrink; Cecilia Geijer (Applied Microbiology and Biotechnology)
Abstract Xylanolytic enzyme systems in ascomycetous yeasts remain underexplored, despite the presence of yeasts in various xylan-rich ecological niches. In this study, we investigated the secreted xylanolytic machineries of three Blastobotrys species—B. mokoenaii, B. illinoisensis, and B. malaysiensis—by integrating genome annotation, bioinformatics, and secretome analyses of cultures grown on beechwood glucuronoxylan. Our findings demonstrate that these yeasts effectively hydrolyze xylan through the secretion of xylanases from the glycoside hydrolase (GH) family 11, which play a central role in cleaving the xylan backbone. Additionally, the yeasts produce a diverse array of other CAZymes, including members of GH families 3, 5, and 67, with putative roles in xylan degradation. We also report on the heterologous expression and functional characterization of the GH30_7 xylanase BmXyn30A from B. mokoenaii, which exhibits both glucuronoxylanase and xylobiohydrolase activities. We demonstrate additive effects between GH family 30 BmXyn30A and GH family 11 BmXyn11A during the hydrolysis of beechwood glucuronoxylan, where the enzymes exhibit complementary roles that enhance the deconstruction of this complex hemicellulose substrate. These findings broaden our understanding of the xylanolytic systems in yeasts and underscore the potential of Blastobotrys species as cell factories and natural xylanase producers. The enzymes they produce hold promise for biorefining applications, enabling efficient utilization of renewable xylan-rich plant biomass resources. Key points • Extracellular GH11 xylanases dominate glucuronoxylan degradation in Blastobotrys yeasts. • Yeast GH30_7 enzyme shows multifaceted activity, supporting complex xylan breakdown. • Blastobotrys yeasts show promise as cell factories for industrial biotechnology applications.